HARD TIMES, HARD CHOICES: FOUNDING BIOETHICS TODAY - Gracia, Diego (Bioethics, 1995)
The discussions of these past twenty years have significantly improved our knowledge about the foundation of bioethics and the meaning of the four bioethical principles with concern to at least three different points: that they are organised hierarchically, and therefore not “prima facie” of the same level; that they have exceptions, and consequently lack of absolute character; and that they are neither strictly deontological nor purely teleological. The only absolute principle of moral life can be the abstract and unconcrete respect of human beings. But when determining the material content of this respect, principles become contingent and relative. Therefore, moral reasoning must have necessarily no less than three moments, one absolute but merely formal, namely respect for all human beings, and the other two relative and material. The first material moment is comprised of the four bioethical principles, divided into two levels, one private, including the principles of autonomy and beneficence, and the other one public, including those of nonmaleficence and justice. The second material moment deals with specific cases, and requires analysis of their context, including their circumstances and consequences. Only when following these steps, and therefore balancing principlism and contextualism, can moral reasoning be correct and complete.